PARTISIPASI MASYARAKAT DAN ANALISIS KELEMBAGAAN LMDH DALAM PROGRAM PENGELOLAAN HUTAN BERSAMA MASYARAKAT DI RPH WANARAJA BKPH CIBATU KPH GARUT - Diaz Aprilian Kosasih; Ilham Adhya; Nina Herlina (Journal of Forestry And Environment, 2022)
This study aims to determine how the level of participation of the Forest Village Community, LMDH Institutional Effectiveness and economic impact analysis in the PHBM system at RPH Wanaraja BKPH Cibatu KPH Garut the sample in this study is the cultivator at LMDH RPH Wanaraja. Data collection in this study used the interview method regarding CBFM program activities at RPH Wanaraja and literature study on CBFM management as well as organizational structure and allocation of profit sharing. The data obtained were analyzed by tabulation to determine the level of participation, as well as the effectiveness of LMDH institutions based on the principles of Good Forest Governance and the economic impact seen from the contribution of CBFM income. at the planning stage some of the cultivators were involved in the planning stage. In the implementation stage, the cultivators are involved in planting, maintaining and protecting the forest. the profit sharing allocation stage is involved in implementing the profit sharing allocation. LMDH institutions are not in accordance with the 4 principles of Good Forest Governance, there is no compatibility between accountability, transparency, democracy and participation. the economic impact of the PHBM program has not yet had an impact on the economy of the cultivators with a percentage of around 6.06% - 25.44% in Wanaraja RPH need further research on the implementation of policies in the PHBM program KPH Garut.Penelitian ini bertujuan untuk mengetahui bagaimana tingkat partisipasi Masyarakat Desa Hutan, Efektifitas Kelembagaan LMDH dan analisis dampak ekonomi dalam sistem PHBM di RPH Wanaraja BKPH Cibatu KPH Garut sampel dalam penelitian ini adalah pembudidaya di LMDH RPH Wanaraja. Pengumpulan data dalam penelitian ini menggunakan metode wawancara mengenai kegiatan program PHBM di RPH Wanaraja dan studi literatur tentang pengelolaan PHBM serta struktur organisasi dan alokasi bagi hasil. Data yang diperoleh dianalisis dengan tabulasi untuk mengetahui tingkat partisipasi, serta efektivitas kelembagaan LMDH berdasarkan prinsip Good Forest Governance dan dampak ekonomi dilihat dari kontribusi pendapatan PHBM. pada tahap perencanaan beberapa pembudidaya terlibat dalam tahap perencanaan. Pada tahap pelaksanaan, penggarap dilibatkan dalam penanaman, pemeliharaan dan perlindungan hutan. tahap alokasi bagi hasil terlibat dalam pelaksanaan alokasi bagi hasil. Lembaga LMDH tidak sesuai dengan 4 prinsip Good Forest Governance, tidak ada kesesuaian antara akuntabilitas, transparansi, demokrasi dan partisipasi. dampak ekonomi program PHBM belum berdampak pada perekonomian para pembudidaya dengan persentase sekitar 6,06% - 25,44% di RPH Wanaraja perlu penelitian lebih lanjut mengenai implementasi kebijakan dalam program PHBM KPH Garut